Effect of a short-term diet and exercise intervention on oxidative stress, inflammation, MMP-9, and monocyte chemotactic activity in men with metabolic syndrome factors - Roberts, Christian K; Won, Dean; Pruthi, Sandeep; Kurtovic, Silvia; Sindhu, Ram K; Vaziri, Nosratola D; Barnard, R. James (Journal of applied physiology (1985), 2006)
1 Department of Physiological Science, University of California, Los Angeles; 2 Division of Endocrinology, Metabolism and Molecular Medicine, Charles R. Drew University, Los Angeles; and 3 Division of Nephrology and Hypertension, Department of Medicine, University of California, Irvine, California Submitted 6 October 2005 ; accepted in final form 14 December 2005 ABSTRACT The present study was designed to examine the effects of lifestyle modification on key contributing factors to atherogenesis, including oxidative stress, inflammation, chemotaxis, and cell adhesion. Obese men ( n = 31), 15 of whom had metabolic syndrome, were placed on a high-fiber, low-fat diet in a 3-wk residential program where food was provided ad libitum and daily aerobic exercise was performed. In each subject, pre- and postintervention fasting blood was drawn for circulating levels of serum lipids, glucose and insulin (for estimation of insulin sensitivity), oxidative stress-generating enzyme myeloperoxidase and marker 8-isoprostaglandin F 2 , the inflammatory protein C-reactive protein, soluble ICAM-1 as an indicator of endothelial activation, sP-selectin as a marker of platelet activation, the chemokine macrophage inflammatory protein-1 , and total matrix metalloproteinase-9. Using subject sera and human aortic endothelial cell culture systems, we measured VCAM-1 cell surface abundance and monocyte chemotactic protein-1, nitric oxide, superoxide, and hydrogen peroxide production in vitro by fluorometric detection. Also determined in vitro was serum-induced, monocyte adhesion and monocyte chemotactic activity. After 3 wk, significant reductions ( P < 0.05) in body mass index, all serum lipids and lipid ratios, fasting glucose, insulin, homeostasis model assessment for insulin resistance, myeloperoxidase, 8-isoprostaglandin F 2 , C-reactive protein, soluble ICAM-1, soluble P-selectin, macrophage inflammatory protein-1 , and matrix metalloproteinase-9 were noted. In vitro, serum-stimulated cellular VCAM-1 expression, monocyte chemotactic protein-1 production, and fluorometric detection of superoxide and hydrogen peroxide production decreased, whereas a concomitant increase in NO production was noted (all P < 0.01). Additionally, both monocyte adhesion ( P < 0.05) and MCA ( P < 0.01) decreased. Nine of 15 were no longer positive for metabolic syndrome postintervention. Intensive lifestyle modification may ameliorate novel coronary artery disease risk factors in men with metabolic syndrome factors before reversal of obesity. atherosclerosis; lipids; cell adhesion molecules; nitric oxide; matrix metalloproteinase-9 Address for reprint requests and other correspondence: C. K. Roberts, Dept. of Physiological Science, UCLA, 4101 Life Sciences Bldg. 621 Charles E. Young Dr. South, Los Angeles, CA 90095-1606 (e-mail: crobertsatucla.edu )